A WORD FROM THE POINT OF VIEW OF LEXICOLOGY AND SYNTAX - I. S. Madrakhimov (Galaxy International Interdisciplinary Research Journal, 2022)
The article presents a positive characteristic of the word from the point of view of lexicology and, based on these data, the signs that distinguish the word from other linguistic units are established.